Predictive capacity of anthropometric indicators for dyslipidemia screening in children and adolescents - Teresa Maria Bianchini de Quadros; Alex Pinheiro Gordia; Rosane Carla Rosendo da Silva; Luciana Rodrigues Silva (Elsevier, 2015)
ABSTRACT OBJECTIVE: To analyze the predictive capacity of anthropometric indicators and their cut-off values for dyslipidemia screening in children and adolescents. METHODS: This was a cross-sectional study involving 1139 children and adolescents, of both sexes, aged 6-18 years. Body weight, height, waist circumference, subscapular, and triceps skinfold thickness were measured. The body mass index and waist-to-height ratio were calculated. Children and adolescents exhibiting at least one of the following lipid alterations were defined as having dyslipidemia: elevated total cholesterol, low high-density lipoprotein, elevated low-density lipoprotein, and high triglyceride concentration. A receiver operating characteristic curve was constructed and the area under the curve, sensitivity, and specificity was calculated for the parameters analyzed. RESULTS: The prevalence of dyslipidemia was 62.1%. The waist-to-height ratio, waist circumference, subscapular, body mass index, and triceps skinfold thickness, in this order, presented the largest number of significant accuracies, ranging from 0.59 to 0.78. The associations of the anthropometric indicators with dyslipidemia were stronger among adolescents than among children. Significant differences between accuracies of the anthropometric indicators were only observed by the end of adolescence; the accuracy of waist-to-height ratio was higher than that of subscapular (p = 0.048) for females, and the accuracy of waist circumference was higher than that of subscapular (p = 0.029) and body mass index (p = 0.012) for males. In general, the cut-off values of the anthropometric predictors of dyslipidemia increased with age, except for waist-to-height ratio. Sensitivity and specificity varied substantially between anthropometric indicators, ranging from 75.6 to 53.5 and from 75.0 to 50.0, respectively. CONCLUSIONS: The anthropometric indicators studied had little utility as screening tools for dyslipidemia, especially in children.